REORIENTASI LGBT DI INDONESIA (STUDI FIQH AL-HADITS) - Mahdalena Nasrun (Institut Agama Islam Negeri Batusangkar, 2017)
Liberal NGOs such as Ardhanary Institute, Gaya Nusantara and Arus Pelangi devoted their bodyfor LGBT with a statement “my body is mine, not the one who has the right to govern my body, notthe parents, the state, and even the religion”. This movement is disturbing the community. Theresearch question of the study was how did LGBT exist in Indonesia? And how does fiqh al hadithview about LGBT. This study used normative legal research. The result of this study revealed that theexistence of LGBT in Indonesia in its history. Prohibition and punishment have been explained inthe book of Tuhfah al Ahwaz , the fatawa of MUI (Indonesian Council of Ulama) (1974, 2014)in line with the criminal code article 292 homosexsual acts, article 4 point 1a of the law onpornography and contradictory to article 1 of law № 1 of 1974 about marriage.